2020
DOI: 10.1108/ijoa-02-2020-2046
|View full text |Cite
|
Sign up to set email alerts
|

Top management teams characteristics and firms performance: literature review and avenues for future research

Abstract: Purpose The purpose of this paper is to review the empirical literature on the relationship between the characteristics of the top management teams (TMTs) and the performance of entrepreneurial firms. Design/methodology/approach A literature review was carried out on 33 empirical studies related to TMTs and performance through analyzing and summarizing the quantitative studies conducted in this area. Findings The results of the literature review show that the relationship between TMTs (demographics and het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 119 publications
(218 reference statements)
0
13
0
Order By: Relevance
“…Third, this study found the moderating effect of team competitive climate between TMT knowledge hiding and TMT creativity. The previous studies have shown that context variables often play an important role in the internal operation of TMT, and the actual effects of TMT operation will be very different under the regulation of the different context variables ( Chen and Liu, 2018 ; Aboramadan, 2021 ). Similar to the research of Černe et al (2014) , this study confirmed that team competitive climate could regulate the influence of TMT knowledge hiding on TMT creativity during the operation of TMT, the difference lied in the fact that team competitive climate was introduced into the specific organizational context of TMT knowledge hiding, and whether team competitive climate helped to adjust the impact of TMT knowledge hiding on TMT creativity.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Third, this study found the moderating effect of team competitive climate between TMT knowledge hiding and TMT creativity. The previous studies have shown that context variables often play an important role in the internal operation of TMT, and the actual effects of TMT operation will be very different under the regulation of the different context variables ( Chen and Liu, 2018 ; Aboramadan, 2021 ). Similar to the research of Černe et al (2014) , this study confirmed that team competitive climate could regulate the influence of TMT knowledge hiding on TMT creativity during the operation of TMT, the difference lied in the fact that team competitive climate was introduced into the specific organizational context of TMT knowledge hiding, and whether team competitive climate helped to adjust the impact of TMT knowledge hiding on TMT creativity.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We know from upper echelons theory that the background of senior leaders, such as their life experiences, values and personalities influence how they interpret and respond to situations for which they need to make decisions. Social, behavioral and cognitive functioning of upper echelon leaders therefore influence their decisions LODJ 44,4 (Bromiley and Rau, 2016), Moreover, from observing the characteristics of strategic leaders, such as their backgrounds, educational levels, ages and years of experience, one may predict how they will make decisions (Aboramadan, 2021). Subsequently, their choices impact organizational performance (Hambrick and Mason, 1984;Friedman et al, 2016;Aboramadan, 2021).…”
Section: Literature Review Upper Echelons Theory and Strategic Leader...mentioning
confidence: 99%
“…Most literature on indecision deals with career indecision (e.g., Lent et al, 2019), or personal traits and indecision (e.g., Ferrari et al, 2018), but very few studies focus on the indecision of leaders and especially upper echelon leaders. A better understanding of the drivers of indecision can shed light on existing models of strategic decision-making (Kokkoris et al, 2019;Aboramadan, 2021). The context of strategic decision-making differs from managerial decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…This breach in the organizational environment leads to gaps in internationalization, environment dynamism, decentralization of power, innovation, growth, international risk management, and behavioral integration (Aboramadan, 2020). The theoretical framework analysis collected the most pertinent information from the publications regarding SP in the 90s.…”
Section: Strict Hierarchy Model (P4)mentioning
confidence: 99%